Liberalism all the way down? - Tadej Košmerl (European Journal for Research on the Education and Learning of Adults)
This paper analyses adult education for sustainable development policies, examining their dominant discursive orientations – neoliberal, liberal, and critical – across global, EU, and national levels. Focusing on Slovenia and its transnational policy influences in this field, it highlights a prevalent interplay of liberal and neoliberal discursive orientations alongside a comparatively limited presence of critical discourse. At the global level, the United Nations’ influence emphasises liberal discourse aligned with Sustainable Development Goals (SDGs), while the European Union policies exhibit a predominant neoliberal discourse, further solidified at the national level, particularly in more recent Slovenian policies. A prevalent interplay of neoliberal and liberal discourses characterises Slovenian adult education for sustainable development policies, reflecting the substantial influence of transnational actors.